Business Zakat conditions and their relationships with accounting principles: An exploratory study - Kadir M.R.A. (Primrose Hall Publishing Group, 2023)
In current practices of business zakat computation, information from financial reporting disclosure is prepared based on accounting principles. However, there are problems as the business zakat conditions require different information from what is being disclosed in financial reporting. This creates difficulties as the current accounting practices cannot fully meet the demand of information required for business zakat computation. As the need of zakat accounting is undeniable, this study goes beyond the normal study by concentrating on each condition of business zakat and how it relates with current accounting practices. It is an exploratory study designed to discuss the current gap between zakat conditions and accounting principles. This study has revealed the gap occurring between the practices are due to two reasons, (i) the different in definition used by the practices and (ii) shariah requirement that is not within the scope of accounting. 2019, Primrose Hall Publishing Group.